Dismantling the NHS? evaluating the impact of health reforms - Exworthy, Mark 1966-; Mannion, Russell; Powell, Martin A. 1961- (Policy Press, 2016)
An in-depth analysis of the NHS reforms ushered in by UK Coalition Government under the 2012 Health and Social Care Act. Essential reading for those studying the NHS, those who work in it and those who seek to gain a better understanding of this key public service.
Keywords: Great Britain. -- National Health Service.